Role of Translocator Protein (18 kDa) in Adult Separation Anxiety and Attachment Style in Patients with Depression - Costa, B.; Pini, S.; Abelli, M.; Gabelloni, P.; Da Pozzo, E.; Chelli, B.; Calugi, S.; Lari, L.; Cardini, A.; Lucacchini, A.; B. Cassano, G.; Martini, C. (Current Molecular Medicine, 2012)
Background and Objectives: A role for the protein that mediates the rate-limiting step of steroidogenesis, the 18 kDa Translocator Protein (TSPO), has been suggested in the pathophysiology of Adult Separation Anxiety Disorder (ASAD). It has been shown that ASAD patients have 1) low TSPO expression levels and 2) a high frequency of the allele that substitutes Ala with Thr at position 147 of TSPO. The Thr147 ASAD-associated allele has been recently related with a low pregnenolone production. The aim of the present work was to evaluate the relationship between TSPO expression levels and Ala147Thr single nucleotide polymorphism (SNP), which are the two TSPO biological parameters that we have previously examined separately. A further aim was to confirm the genetic association of Ala147Thr SNP with ASAD in an extended case-control sample and to investigate whether this SNP was related to an anxious attachment style that is thought to be connected to ASAD. Methods: TSPO expression levels were compared among patients with ASAD (n=26), without ASAD (n=26) and control samples (n=10) stratified into the two genotype groups: those with the Ala147 genotype (named “normal pregnenolone production”) and those with the Thr147 genotype (named “reduced pregnenolone production”). The case-control genetic study included patients with (n=87) or without (n=101) ASAD and 236 controls. In the patient group, the association between the Ala147Thr SNP and an anxious attachment style was analysed by stepwise logistic regression analysis. Results: The genotype with the lowest TSPO expression levels was the “normal pregnenolone production” genotype in the ASAD group. The genetic Ala147Thr SNP confirmed an excess of the Thr147 allele in ASAD patients. Stepwise logistic regression analysis did not show an association with an anxious attachment style. Conclusions: ASAD individuals who expressed normal TSPO levels exhibited the “reduced pregnenolone production” genotype. In contrast, the ASAD individuals with the “normal pregnenolone production” genotype expressed low TSPO levels. It is possible that low TSPO expression levels could compromise normal pregnenolone production. Such evidence may have therapeutic implications because it has been documented that drugs targeting TSPO increased pregnenolone production and have anxiolytic effects.
Keywords: cholesterol